2008
DOI: 10.1128/cvi.00132-08
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity between Immune Responses to Helicobacter bilis and Helicobacter pylori in a Population in Thailand at High Risk of Developing Cholangiocarcinoma

Abstract: Helicobacter bilis DNA has been detected in human tissue and is a candidate for etiologic investigations on the causes of hepatic and biliary tract diseases, but reliable serologic tests need to be developed in order to pursue such investigations. The scope of this study was to assess the specificity of two assays for H. bilis immune response allowing for H. pylori, and their cross-reactivity in a population in Thailand at high risk for cholangiocarcinoma. Plasma samples from 92 Thai volunteers were independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…4). Interestingly, given the importance of macrophages in chemokine production (e.g., Cxcl1) and neutrophil influx during IBD and other inflammatory states (6,34,41,46), the systemic depletion of macrophages in H. bilis-infected Rag2 Ϫ/Ϫ mice in the present study also resulted in a significant reduction (P Ͻ 0.015) in cecal neutrophil counts compared to their placebo (PBS) liposome-treated counterparts (Fig. 4).…”
Section: Systemic Macrophage Depletion Attenuated Typhlocolonic Inflasupporting
confidence: 50%
See 1 more Smart Citation
“…4). Interestingly, given the importance of macrophages in chemokine production (e.g., Cxcl1) and neutrophil influx during IBD and other inflammatory states (6,34,41,46), the systemic depletion of macrophages in H. bilis-infected Rag2 Ϫ/Ϫ mice in the present study also resulted in a significant reduction (P Ͻ 0.015) in cecal neutrophil counts compared to their placebo (PBS) liposome-treated counterparts (Fig. 4).…”
Section: Systemic Macrophage Depletion Attenuated Typhlocolonic Inflasupporting
confidence: 50%
“…H. bilis is also associated with proliferative typhlocolitis, chronic hepatitis, hepatic dysplasia, and biliary hyperplasia in aged Syrian hamsters (14), as well as IBD/colitis in athymic nude rats (20). Further, H. bilis has been incriminated to play a role in human cholecystitis and gallbladder cancer from studies in Japan, Thailand, and Chile (11,24,34). In immunocompetent mice (C3H) mice with defined microbiota, H. bilis infection-even in the absence of overt colitis-results in a significant increase in the expression pattern of a plethora of mucosal genes, including those involved in lymphocyte activation (e.g., Cd28 and Tnfsf13b) and regulation (e.g., Il-17a) and in inflammatory cell chemotaxis (e.g., Itgb2, Ccl8, and Ccr5) (27).…”
mentioning
confidence: 99%
“…H. pylori and H. bilis DNA has been isolated from liver tissue of humans with CCA and cholecystitis/cholelithiasis from Thai patients living in regions endemic for opisthorchiasis (Boonyanugomol et al 2012b; 2012c). Moreover, serological assays indicate active infection with H. pylori and H. bilis in Thais at high risk for CCA (Pisani et al, 2008). H. bilis was also associated with biliary cancers in two high-risk populations in Japan and Thailand (Matsukura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In two studies from India and China, colonisation by Helicobacter was shown in the gallbladder epithelium, especially in the areas of gastric metaplasia (Chen et al, 2007;Misra et al, 2007), but it is not known whether this was merely a consequence of tissue damage. Serological studies have not been reviewed here, but cross-reactivity between the immune response to antigens from H. pylori and H. bilis has been reported (Ananieva et al, 2002;Pisani et al, 2008). Furthermore, it has been shown that the prevalence of serological and histological markers of H. pylori decreases in gastric cancer (Camorlinga-Ponce et al, 2008) and it is not known whether the same happens in BT cancer.…”
Section: Discussionmentioning
confidence: 99%